Effects of whole plant brown algae (Laminaria japonica) on zootechnical performance, apparent total tract digestibility, faecal characteristics and blood plasma urea in weaned piglets. Issue 1 (2nd January 2020) - Brugger, Daniel; Bolduan, Carmen; Becker, Christiane; Buffler, Marzell; Zhao, Jie; Windisch, Wilhelm M.
ABSTRACT: Two trials were conducted with 48 newly weaned piglets (28 d old) each 8.6 ± 0.05 kg to study how Laminaria japonica plants ( LJ ) affect zootechnical performance, feed conversion and the apparent total tract digestibility (ATTD) of crude nutrients. All basal diets consisted of cereals, soybean meal, skim milk powder and premixes according to recommendations (no growth promoters or enzymes). For Trial 1, piglets from 16 litters (50% male-castrated, 50% female) were assigned to three treatment groups ( n  = 16) in a completely randomised block design. Groups received either 2.5% supplementation with sun dried (SD) or drum dried (DD) LJ powder or 2.5% of diatomaceous earth (control). For Trial 2, piglets from 12 litters received either 5% of diatomaceous earth (control) or one of three mixtures of diatomaceous earth + DD LJ powder (3.3%+1.7%, 1.7%+3.3% or 0.0%+5%; n = 12). Data collection included zootechnical performance, faecal consistency, blood plasma urea (Trial 1 and 2) and ATTD (Trial 2). Metabolisable energy (ME) of DD LJ and diets in Trial 2 was estimated using digestible nutrients. Statistical analysis included two-way ANOVA (treatment, block) and mixed linear regression. During both trials, LJ at dosages ≥2.5% significantly reduced feed:gain ratio compared to control ( p ≤ 0.0001, = 0.01 for Trial 1, Trial 2) irrespective of the drying method. ATTD from Trial 2 significantly increased digestibilities of dry matter (DM) and crude ash (CA) ( p ≤ 0.01) and significantly decreased digestibilities of organic matter and crude fibre in animals fed ≥3.33% DD LJ ( p = 0.01). Fractional digestibility of the DD LJ resulted in limited ME of ~9.3 ± 2.5 MJ/kg DM. Dietary conversion ratios of ME and digestible DM of DD LJ diets from Trial 2 decreased linearly with increasing algal supplementation (R 2  = 0.93, 0.94 and p slope  = 0.002, 0.002 for MCR, DCR). In conclusion, dried LJ powder was included up to 5% into diets without impairing zootechnical performance. The improved feed conversion in the presence of LJ was partly due to slightly higher ME within the algae diets compared to control. However, piglets receiving LJ during Trial 2 needed significantly lower dietary ME and digestible DM to maintain growth performance. Thus, LJ exerted a performance enhancing effect on weaned piglets. The precise mode-of-action is yet unclear.